1999
DOI: 10.1177/03635465990270021501
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Matched Bone-Patellar Tendon-Bone and Double-Looped Semitendinosus and Gracilis Tendon Grafts

Abstract: Biomechanical testing was done on 15 matched pairs of central-third bone-patellar tendon-bone and double-looped semitendinosus-gracilis grafts harvested from 15 cadaveric knees. Load to failure, composite graft stiffness, and the modulus of elasticity were calculated for each graft. Specimens were from 2 female and 13 male donors (average age, 40 years; range, 17 to 53). Average load to failure for the patellar tendon grafts was 1784 N (+/- 580), compared with 2422 N (+/- 538) for the hamstring tendon grafts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 22 publications
5
123
3
5
Order By: Relevance
“…At this time point, the average stiffness values for the hamstring tendon and patella tendon grafts were 174 and 159 N/mm, respectively. Although the stiffness was measured over a relatively small range of displacement, the stiffness values were within the range of some previously recorded stiffness values for quadruple strand hamstring tendon graft constructs (119 to 189 N/mm 11,20,21 ) and patella tendon grafts (158 to 219 N/mm 20,22,23 ). As described previously, 12 the deformation was chosen to measure stiffness without inducing slippage at the fixation sites that could have influenced the tension measurements.…”
Section: Comparison Of Graft Tension and Stiffnesssupporting
confidence: 71%
“…At this time point, the average stiffness values for the hamstring tendon and patella tendon grafts were 174 and 159 N/mm, respectively. Although the stiffness was measured over a relatively small range of displacement, the stiffness values were within the range of some previously recorded stiffness values for quadruple strand hamstring tendon graft constructs (119 to 189 N/mm 11,20,21 ) and patella tendon grafts (158 to 219 N/mm 20,22,23 ). As described previously, 12 the deformation was chosen to measure stiffness without inducing slippage at the fixation sites that could have influenced the tension measurements.…”
Section: Comparison Of Graft Tension and Stiffnesssupporting
confidence: 71%
“…In addition, Hamner et al 1 showed that combined 4-strand hamstring grafts were stronger and stiffer with greater load to failure than historical results with BPTB autograft. In a similar study by Wilson et al, 2 superior load-to-failure results were confirmed with 4-strand hamstring autograft (2,422 N) compared with matched BPTB autograft (1,784 N). …”
Section: Discussionmentioning
confidence: 58%
“…In addition, biomechanical testing of 4-strand gracilis and semitendinosus autograft has shown a higher load to failure than that with BPTB autograft. 1,2 Most importantly, clinical outcomes have been equivalent using 4-strand hamstring autograft and using BPTB autograft. 3 A potential disadvantage of hamstring autograft for ACL reconstruction is the inherent variability in graft diameter (Table 1).…”
mentioning
confidence: 99%
“…Bone-patellar tendon-bone (BPTB) autografts have been proclaimed as the "gold standard" in ACL reconstruction (Woo et al, 2006). Biomechanically, a 10-mm wide BPTB graft has stiffness and ultimate load values of 210 ± 65 N/mm and 1784 ± 580 N, respectively (Wilson et al, 1999), which compare well with those of the young human femur-ACL-tibia complex (242 ± 28 N/mm and 2160 ± 157 N, respectively), (Woo et al, 2006). It also shows the advantage of having bone blocks available for graft fixation in the osseous tunnels that leads to better knee stability.…”
Section: Autologous Tendon For Torn Acl Replacementmentioning
confidence: 70%